The Predictive Power of Students' Metacognition and Perceptions of Instructional Competencies of Instructors on Academic Life Satisfaction - İbrahim Tuncel; Zeynep Ayvaz-tuncel (e-Kafkas Eğitim Araştırmaları Dergisi)
Change and development in university education is shaped by a complex interplay of environmental factors and individual efforts. Students' awareness of their cognitions, the instructors they interact with, and their qualifications play an essential role in this development and change process and determine academic life satisfaction. This study aims to assess the metacognitive skill perception of university students and their perceptions of instructors' instructional competencies and to reveal the predictive power of these two variables on academic life satisfaction. The practical implications of this study can empower educators and students to enhance academic life satisfaction. Based on the relational survey model, the data were obtained from 405 students at the Faculty of Humanities and Social Sciences at a state university in Turkiye. Academic Life Satisfaction Scale, Metacognitive Skill Perceptions Scale, and Instructor’s Instructional Competence Scale were used to collect data. In the data analysis, the Pearson Product Moment Correlation coefficient was calculated to examine the relationship between the scores obtained from the scales. Hierarchical Regression Analysis was used to solve the sub-problems related to prediction. The hierarchical regression included the student's achievement perception as a control variable. As a result of the data analysis, it was identified that there was a moderate positive significant relationship between students' academic life satisfaction and their perception of instructors' instructional competencies and metacognitive skill perception levels. When the students' achievement perceptions were controlled, it was determined that metacognitive skill perception explained 15% of academic life satisfaction. When achievement perception and metacognitive skill perception were controlled, it was found that the perception of the instructor's instructional competence explained 10% of academic life satisfaction. Based on the research findings, it was concluded that the effect of students' metacognitive skill perception on academic life satisfaction was higher than their perceptions of the instructor's instructional competence.